2021
DOI: 10.1021/acsami.1c06637
|View full text |Cite
|
Sign up to set email alerts
|

Strong Foam-like Composites from Highly Mesoporous Wood and Metal-Organic Frameworks for Efficient CO2 Capture

Abstract: Mechanical stability and multicycle durability are essential for emerging solid sorbents to maintain an efficient CO 2 adsorption capacity and reduce cost. In this work, a strong foam-like composite is developed as a CO 2 sorbent by the in situ growth of thermally stable and microporous metal-organic frameworks (MOFs) in a mesoporous cellulose template derived from balsa wood, which is delignified by using sodium chlorite and further functionalized by 2,2,6,6-tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 68 publications
(158 reference statements)
0
19
0
Order By: Relevance
“…Ma et al used nanobacterial cellulose (NBC) as a template for amino-functionalized ZIF-8 (NH2-ZIF-8) and reported a high CO2 adsorption capacity of 1.63 mmol g −1 at 25 °C and 1 bar [30]. Wang et al studied a TEMPO-oxidized wood (TOwood) template for three types of MOFs [31]. They reported that the TO-wood/Cu3(BTC)2 presents a mechanically robust composite with a high specific surface area of 471 m 2 g −1 and a high CO2 adsorption capacity of 1.46 mmol g −1 at 25 °C and atmospheric pressure [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al used nanobacterial cellulose (NBC) as a template for amino-functionalized ZIF-8 (NH2-ZIF-8) and reported a high CO2 adsorption capacity of 1.63 mmol g −1 at 25 °C and 1 bar [30]. Wang et al studied a TEMPO-oxidized wood (TOwood) template for three types of MOFs [31]. They reported that the TO-wood/Cu3(BTC)2 presents a mechanically robust composite with a high specific surface area of 471 m 2 g −1 and a high CO2 adsorption capacity of 1.46 mmol g −1 at 25 °C and atmospheric pressure [31].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al studied a TEMPO-oxidized wood (TOwood) template for three types of MOFs [31]. They reported that the TO-wood/Cu3(BTC)2 presents a mechanically robust composite with a high specific surface area of 471 m 2 g −1 and a high CO2 adsorption capacity of 1.46 mmol g −1 at 25 °C and atmospheric pressure [31]. The morphological characteristics of the substrate could significantly affect the adsorption behavior of this class of composites.…”
Section: Introductionmentioning
confidence: 99%
“…Vast work among the academic community has been taken to alleviate the negative effect of the rapid growth of atmospheric CO 2 concentration at a global level, such as developing renewable and clean energies [3][4][5] and functional porous materials [6,7], and decades of research and projects on carbon capture, utilization and sequestration (CCUS) [8][9][10] have been conducted to reduce the influence of carbon emission. And various solid absorbents, such like activated carbon (AC) [11][12][13][14], molecular sieve [15,16], metal oxides [17] and MOF [18], Among these products, ACs have been widely applied in carbon dioxide capture due to their special pore structure, specific surface area and chemical stability, and simple processing; tremendous research efforts have focused on the adsorption capacity, selectivity and renew-ability of activated carbon products [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The N 2 adsorption isotherm (Figure 2c) reveals a type IV isotherm and H 4 hysteresis loop. 22 A specific surface area of 2.16 m 2 g −1 , together with a wide pore distribution range from mesopores to macropores as defined by the International Union of Pure and Applied Chemistry (IUPAC), can be derived from the SEM observation and N 2 adsorption data. 23 The hierarchal pores and larger surface area in 450 °C + NaClO 2 wood can provide channels for ion transfer and electrolyte infiltration; thus, a large ion storage capacity could be anticipated based on the inherent structural advantages in the 450 °C + NaClO 2 wood electrode.…”
mentioning
confidence: 99%
“…Scanning electron microscope (SEM) images in Figure b and Figure S4 show that the 3D-wood electrode presents a hierarchical porous structure. The N 2 adsorption isotherm (Figure c) reveals a type IV isotherm and H 4 hysteresis loop . A specific surface area of 2.16 m 2 g –1 , together with a wide pore distribution range from mesopores to macropores as defined by the International Union of Pure and Applied Chemistry (IUPAC), can be derived from the SEM observation and N 2 adsorption data .…”
mentioning
confidence: 99%